Finansowanie działalności inwestycyjnej jednostek samorządu terytorialnego - Krasucka, Maja; Pieczonka, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
An investition activity of the self-government units is characterised by realising indispensable public aims. Well done investition process, in long term, determining level of technical and social infrastructure development, is indispensable condition of local and regional economical development. In conditions of high, quantitative and qualitative, investition needs well done finance project, based on economical-social accountment, is one of the main factor determining making and realising self- government investition activity. Because of these in this article used sources of financing investition activity of self-government units are presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 490-499